فعالية النظام الضريبي في حماية البيئة من أشكال التلوّث دراسة تحليلية لنموذج الضريبة البيئية في الجزائر. - بن عـزة, د. محمد (Recherches économiques et managériales; Vol. 19 (2016): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (JUIN), 2016)
من خلال  الورقة البحثية تطرقنا إلى دور النظام الضريبي في حماية البيئة من التلوث من خلال التشريعات الجبائية الرادعة للملوثين، والتركيز على أهم المفاهيم المتعلقة بالجباية البيئية في التشريعات المغاربية (خاصة تونس، الجزائر ، المغرب) ، بالإضافة إلى دراسة نموذجية لرؤية المشرع الجزائري في ما يخص الجباية البيئية ومدى فعاليتها في الحد من التلوث الذي يواجه البيئة في الجزائر.          وخلصت الدراسة إلى ان الجباية البيئية تساهم في التقليل من التلوث بشرط دراسة جيدة لمعدلات وتوقيت فرضها لأن لها أهمية كبيرة في تحقيق الأهداف المحددة  مسبقا. الكلمات المفتاحية : البيئة، التلوث، النظام الجبائي، الجباية البيئية، الجزائر . Abstract :                We will try through the research paper that discussed the role of the tax system to protect the environment from pollution through legislation tax deterrent to polluters, and focus on the most important concepts related to Paljbaah environmental legislation in the Maghreb (especially Tunisia, Algeria, Morocco), in addition to the pilot study to see the Algerian legislature in terms of environmental taxes and their effectiveness in reducing pollution, facing the environment in Algeria.       This study concluded that the environmental taxes contribute to the reduction of pollution, It provided a good study of the rates and timing imposed . Because they have a great importance in achieving the desired  objectives Keywords : environment, pollution, taxe system, environmental taxes, Algeria.